The synthesis of single-phase yttrium iron garnet doped zinc and some structural and magnetic properties. (30th January 2017) - Peña-Garcia, R; Delgado, A; Guerra, Y; Duarte, G; Gonçalves, L A P; Padrón-Hernández, E
Abstract: This work presents the single phase formation of yttrium iron garnet (YIG) doped with divalent Zn ions in samples fabricated by the sol–gel method and heat treated at 900 °C. We used stoichiometric amounts according to the formula Y3 (Fe1− x Zn x )5 O12, ( x   =  0, 0.01, 0.03 and 0.05). The x-ray diffraction data show the single phase formation with the lattice parameter increasing with the Zn concentration. The scanning electron microscopy images showed nanoparticles with a rod format, crowding more as the doping increased. Energy dispersive x-ray spectroscopy results confirmed the presence of Zn in the YIG structure. The Raman spectroscopy measurements show characteristic peaks of the YIG structure, and some characteristic peaks increasing with the Zn concentration. This confirms our successful result doping the YIG structure with the divalent Zn ion replacing the Fe positions. Magnetic measurements show coercive field values dominated by the shape and agglomeration of nanoparticles. For low doping we have a value of 88.50 Oe attributed to the particles' morphology, and for the highest Zn concentrations the effects of agglomeration diminish the coercivity to 50 Oe. The total magnetic moment for low Zn concentrations increases slightly due to the replacement of Fe by Zn. For higher Zn concentrations, we can see a diminution of the magnetic saturation which is due to the growth of the crystal lattice parameter and thus a weakening of the exchange interactions between the magnetic sub-lattices in the Y3 (Fe1− x Zn x )5 O12 ferrimagnetic compound. Changes in the magnetic moment do not have large values, showing the possibility of doping without a drastic change in this quantity.